Knowledge gaps in protected area effectiveness. (30th July 2013) - Cabeza, M.
<x xml:space="preserve">Abstract</x> Read the Feature Paper: Protected areas and insect conservation: questioning the effectiveness of Natura 2000 network for saproxylic beetles in Italy Other Commentaries on this paper: Institutional vertebratism hampers insect conservation generally; not just saproxylic beetle conservation Response from the authors: Possible directions in the protection of the neglected invertebrate biodiversity